Comparison of functional outcome and quality of life following treatment of unstable intertrochanteric fractures with intramedullary nailing and dynamic hip screw - Anil Kumar Reddy; R. Chandra Sekhar Reddy (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2019)
Background: The dynamic hip screw is considered as the standard treatment for Intertrochanteric fracture. The procedure per se requires long term hospitalization and other complications. Researchers have proposed intramedullary nailing as an alternate procedure. The present study aims to compare the radiological and functional outcome following treatment of unstable intertrochanteric fractures with intramedullary nailing and dynamic hip screw and to compare Health-related quality of life between the two treatment methods.Methods: A prospective observational study was conducted during March 2014 to July 2016. Patients presenting with unstable Intertrochanteric fractures were recruited prospectively. The study was conducted in the department of orthopedics, Rajiv Gandhi Institute of medical sciences, Kadapa, which is a tertiary care teaching hospital. The participants were divided into two groups. Group, I constitute 25 patients who underwent DHS and Group II had 23 patients who underwent IHN. The mean age of Group DHS participants were 71.45.86 years, and group IMN participants were 69.76.13 years. The mean intraoperative bleeding of subjects in DHS group was325.2467.32 (in ml) and it was 325.2467.32 (in ml) in IMN group.Results: The mean time taken for the radiological union of subjects in DHS group was22.3 1.73 weeks, and it was 20.62.13 weeks in IMN group.Conclusions: The treatment of unstable Intertrochanteric fracture can be done in geriatric patients through surgical intervention without much morbidity and mortality. The postoperative quality of life returns to near normal at the end of one year period.